"Who Leaves Home If There is a Choice?": Migration Decisions of Women Workers on Tea Plantations in India. Issue 2 (1st June 2021) - Banerjee, Supurna
Abstract: The Dooars tea plantations in India were colonial enterprises set up through recruiting a migrant workforce from Central India. Against the background of the crisis in the Indian tea industry in the early 2000s, and the resulting migration of workers to the cities to join various casual workforces, this article questions the dualities in the framework of migration/displacement and aspiration/ desperation. Through mapping the migration decisions of women workers from the plantations, the article traces the ways in which aspiration often follows from migration rather than predating it. Inheriting a history of displacement as migrant labor brought from Central India, the aspiration expressed is often that of belonging. The article then interrogates how the narratives of displacements feature in narratives of aspiration. The migration strategies are not uniform among all the women, but vary across their life stages and accordingly the possibilities and limitations post-migration differ.